DIGITALISASI LAYANAN BIMBINGAN KARIER: METODE DESIGN THINKING DALAM PENYUSUNAN LEARNING MANAGEMENT SYSTEM RUANG KARIER - Anggi Jatmiko; Al Riza Ayurinanda; Erina Dian Florentina; Rahmi Nur Safitri (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2023)
Digitalization of Career Services: Design Thinking Method in Developing Learning Management System for Career Space. Career services at the senior high school level play an important role in helping learners plan advanced careers. Learners need to understand their potential to be able to plan and make advanced career decisions. The limited time and hours of counseling services at school is one of the obstacles for counseling teachers in providing career services thoroughly. In addition, there are still many students who do not understand their potential, so they are not able to plan and make career decisions. BK teachers in schools need career service media that can accommodate the career service needs of students. This research aims to design a digital-based career service media using a learning management system (LMS) that contains literature related to college information, majors, considerations about self-potential and accumulates these data as consultation materials for counseling teachers. This research is a qualitative descriptive study using the design thinking method in designing the career space LMS. In design thinking there are five phases, namely, empathize, define, ideation, prototype, and test. The results of the design with the design thinking method carried out, in the Career Room LMS there are three courses, namely career exploration, career planning and career decision making. (1) Career exploration contains career-related information. (2) Career planning contains RIASEC, DISC and multiple intelligence personality tests. (3) Career decision making is a digital-based consultation room.   Keywords: Career Services, Design Thinking Method, Learning Management System.